A Sharia Economic Law Review of the Contract for the Use of the Duha Syariah Application - Khairul Amri; Muhammad Hakim Ramadhan; Fahmi Taupik Hidayat; Jaenudin J; Dian Herdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The covenant is a fundamental pillar in the Islamic economic structure (muamalah), whose essence is to ensure that all transactions run fairly and are free from prohibited practices, especially riba, gharar (uncertainty), and maisir (speculation). Digital disruption through Financial Technology (Fintech) gives rise to innovations such as Fintech Syariah, which includes a Sharia-based Peer-to-Peer Lending (P2P Lending) platform, one of which is Duha Syariah. This study focuses on an in-depth analysis of the compatibility of the agreements implemented by Duha Syariah with the framework of Sharia Economic Law, especially referring to the DSN-MUI Fatwa No. 117/DSN-MUI/II/2018 and the regulation of the Financial Services Authority (OJK) through POJK No. 10/POJK.05/2022. By using a normative legal approach, the research results indicate that Duha Syariah which has obtained official permission from OJK and is under the supervision of the Syariah Supervisory Board (DPS) consistently applies commercial agreements such as Murabahah (for goods-based financing) and Ijarah (for financing services), as well as the Wakalah bil Ujroh agreement in the platform's operational scheme. This transaction model rigidly requires the existence of a clearly identified underlying asset (specified), so that it is substantively able to nullify the element of usury.